Teknologi Informasi, Partisipasi Manajemen, Dan Kemampuan Pemakai Sistem Informasi Akuntansi Terhadap Kinerja Karyawan Bagian Akunatansi - Choyrul Anuar; Darman Usman (JURNAL FAIRNESS, 2021)
This study aims to examine the influence of information technology, management participation, and the ability of users of accounting information systems on the performance of accounting employees. This study uses a quantitative approach. Respondents in this study were 40 accounting employees at the automotive company in the city of Bengkulu. This study collected primary data with a questionnaire. The selection of samples tested in this study using purposive sampling. The data were analyzed by using multiple linear regression analysis with SPSS program. The results show the management participation has a positive effect on the performance of accounting employess,but information technology no influence on the performance of employees in the accounting department, and the ability of users of accounting information systems no influence the performance of employees in accounting,